Eigenvalues of a third order BVP subject to functional BCs - Infante, Gennaro; Lucisano, Paolo (Topological Methods in Nonlinear Analysis, 2026)
We discuss the existence of eigenvalues for a third order boundary value problem subject to functional boundary conditions and higher order derivative dependence in the nonlinearities. We prove the existence of positive and negative eigenvalues and provide a localization of the corresponding eigenfunctions in terms of their norm.The methodology involves a version of the classical Birkhoff-Kellogg theorem. We illustrate the applicability of the theoretical results in an example.